Assessment of the effect of alpha-tocopherol on the course of newly diagnosed pulmonary sarcoidosis: a comparative study - Vizel, A. A.; Culver, D. A.; Vizel, I. Yu; Shakirova, G. R.; Bakunina, E. A. (Tuberkulëz i bolezni lëgkikh, 2020)
The objective: to compare the results of follow-up over patients with a mild form of pulmonary sarcoidosis who received alpha-tocopherol and those receiving no treatment. Subjects and methods. The results of follow-up over 80 sarcoidosis patients were retrospectively analyzed – two groups of 40 patients enrolled according to the copy – pair principle (gender, age, initial X-ray stage, Löfgren syndrome, and follow-up duration). The only sign that statistically distinguished the groups was a high frequency of complaints about weakness in those who received vitamin E – 55% versus 30% (p < 0.05). The follow-up period for patients in both groups was a year or more (a control point). The database was maintained and processed using SPSS-18, Windows 10. A clear advantage of vitamin E administration was revealed when comparing the data of computed tomography, which resulted in improvement in 87.5%, and the disease progressed in 2.5%, while in the group receiving no treatment – 60 and 12.5%, respectively. The OR of improvement in computed tomography with alpha-tocopherol versus the group receiving no treatment made 4.67 (95% CI, 1.51-14.46). Conclusion. The use of vitamin E in mild forms of thoracic sarcoidosis gives a better result compared to the group receiving no treatment.